Non-conventional advertising formats in television versus spots: An analysis based on the generated recall - Reinares-Lara, Eva; Reinares-Lara, Pedro; Olarte-Pascual, Cristina (Historia y Comunicación Social, 2016)
Advertising investment and audience figures indicate that television continues to lead as a mass advertising medium. However, its effectiveness is questioned due to problems such as zapping, saturation and audience fragmentation. This has favoured the development of non-conventional advertising formats. This study provides empirical evidence for the theoretical development. This investigation analyzes the recall generated by four non-conventional advertising formats in a real environment: short programme (branded content), television sponsorship, internal and external telepromotion versus the more conventional spot. The methodology employed has integrated secondary data with primary data from computer assisted telephone interviewing (CATI) were performed ad-hoc on a sample of 2000 individuals, aged 16 to 65, representative of the total television audience. Our findings show that non-conventional advertising formats are more effective at a cognitive level, as they generate higher levels of both unaided and aided recall, in all analyzed formats when compared to the spot.
Keywords: Non-conventional television advertising; new forms of television advertising; spots; television advertising; advertising effectiveness; advertising recall